Pengaruh Green Accounting, Ukuran Perusahaan, Dan Leverage Terhadap Financial Performance Dengan Nilai Perusahaan Sebagai Variabel Moderasi - Mabruroh Mabruroh; Saiful Anwar (Journal of Economic, Bussines and Accounting (COSTING), 2022)
This study aims to examine and analyze the effect of green accounting, firm size, and leverage on financial performance with firm value as a moderating variable. The population used in this study are companies producing raw materials consisting of the mining sector and the agricultural sector which are listed on the Indonesia Stock Exchange for the 2016-2020 period. Purposive sampling technique is the technique used for sampling with a total of 17 companies. Warp PLS version 8.0 is used to support research data analysis. The results of this study are green accounting is not related to financial performance, firm size has a negative effect on financial performance, leverage is positively related to financial performance, firm value strengthens the relationship between green accounting and financial performance, firm value cannot moderate the relationship between firm size and financial performance. performance, firm value strengthens the relationship between leverage and financial performance. Keywords : Green Accounting, Firm Size, Leverage, Financial Performance, Firm Value.